Creating a Medieval Spatial Myth: Perception of the Body on the Alischanz Battlefield - Greenfield, John (Cadernos de Literatura Comparada, 2016)
It has been noted that in the Middle Ages space and time were considered not as abstractions, but in concrete terms: thus, the bond between man’s body and nature determined his perception of space, as space was measured by the human body. In this paper, I will discuss the extent to which, in the medieval narrative, the perception of space is achieved through the body; I will do this by analysing the spatial dimensions of the battlefield in one of the major epic poems of the German courtly period, Wolfram von Eschenbach’s Willehalm. The organization of space in this work is characterised by specifically medieval thinking patterns: thus, in keeping with courtly literary convention (in which topographical and ‘naturalistic’ elements have a very specific, often symbolic meaning), Wolfram does not describe the battlefield landscape in any great detail. In his text, the space of the battlefield is primarily constituted through the perception of the knight’s body: thus, the poet makes use of the warriors’ senses of sight, hearing, touch, smell and taste in order to provide spatial meaning – and to create a spatial myth.